Strategi Pembentukan Karakter Religius Peserta Didik Melalui Kegiatan Keagamaan - Marzuki, Moh. Hamim; Imron, Ali (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2023)
This study aims to describe strategies for forming students' religious values through religious activities at Muallimin Islamic Middle School Kepung Kediri. This research is research using a qualitative approach and descriptive research type. Data collection techniques using observation, interviews, and documentation. The results of the research are; (1) religious values at Muallimin Islamic Middle School Kediri Kediri are classified into values of conscience (moral values) including pious, polite, friendly, honest, disciplined, respectful time, responsible, sincere, and humble. While scoring (Values of Giving) includes: empathy for each other, collecting donations to help friends, respecting the opinions of others, helping, and communicating. (2) Strategies for forming religious character through religious activities include Example, Instilling Discipline, Habituation, Creating a Conducive Atmosphere, Integration and Internalization, and Touch-heart. (3) The implementation of the formation of religious character through religious activities that took place at the Islamic Middle School Muallimin Kepung Kediri has been going well, namely by doing dhuha and midday prayers in congregation, reading the Koran, hut romadhon, PHBI, istighotsah and praying in congregation. the beginning and end of the lesson.